(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
This article discusses the system of forming a sense of national pride in students by means of ethno-pedagogical values, and special emphasis is placed on the issues of educating our young people to be mature in all aspects and raising the sense of patriotism in today’s dangerous times.